Reducing food safety errors in the United States: Leader behavioral integrity for food safety, error reporting, and error management. (October 2016) - Guchait, Priyanko; Neal, Jack A.; Simons, Tony
Abstract: This paper addresses the challenge of reducing food safety errors in the foodservice industry. Results of a survey of 255 fulltime food service professionals supported our proposed causal chain of impact that runs from "leader behavioral integrity for food safety" (the extent to which leaders/supervisors consistently enact and enforce food safety rules) through the proportion of food safety errors reported, through "error management" (an integrated set of practices involving error detection, correction, analysis, prevention and learning), finally to reduced food safety violations. Specifically, this study found the mediating effect of error reporting between leader behavioral integrity for food safety and error management; and the mediating effect of error management between error reporting and food safety violations. Results suggest that ongoing support and incentivizing of supervisors' behavior may be a critical supplement to skill-based training of employees in reducing food safety errors and thus violations. The study found that high leader behavioral integrity for food safety can improve error reporting and error management leading to a reduction in the risk of foodborne illness, which is the ultimate goal of a food safety training program. It is recommended that managers serve as role models by following proper food safety practices and reporting errors themselves. A manager who consistently enacts food safety priorities and protocols conveys more clear information about positive organizational priorities for safety, provides clearer incentives for safety behaviors, models desired attitudes, and enhances employee trust and thus willingness to learn; which is critical for the success of food safety programs.